2016
DOI: 10.35248/2684-1320.16.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Therapeutic Efficacy of Vinpocetine in Adjuvant Induced Arthritis Model in Rats

Abstract: Introduction: Rheumatoid Arthritis (RA) is an incurable chronic inflammatory disorder. Indomethacin is used for symptomatic management of RA; its long term use is associated with potentially life-threatening deleterious side effects. Vinpocetine is an alkaloid extracted from the periwinkle plant used for treating cerebrovascular disorders with no significant side effects. Recent evidences demonstrate its anti-inflammatory properties.Objective: To evaluate the anti-inflammatory, analgesic and neuroprotective ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In addition, it was demonstrated that in RA, macrophages, fibroblast-like synoviocytes and activated T cells produced pro-inflammatory mediators, as interleukin-1 beta (IL-1β) and TNF-α, which played key roles in the pathogenesis of RA [31] . These cytokines might be involved in promoting inflammation, synovial tissue hyperplasia and osteoclast differentiation [32] . Also, IL-1β and TNF-α might stimulate chondrocytes and osteoclasts to release the cartilage and bone-destroying metalloproteinases [33] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that in RA, macrophages, fibroblast-like synoviocytes and activated T cells produced pro-inflammatory mediators, as interleukin-1 beta (IL-1β) and TNF-α, which played key roles in the pathogenesis of RA [31] . These cytokines might be involved in promoting inflammation, synovial tissue hyperplasia and osteoclast differentiation [32] . Also, IL-1β and TNF-α might stimulate chondrocytes and osteoclasts to release the cartilage and bone-destroying metalloproteinases [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Vincamine (enrichment score = 0.53 and p = 4.21 × 10 −02 ) was previously shown to prevent inflammation induced by lipopolysaccharide in a human corneal epithelial cell line [ 51 ]. A synthetic derivative of vincamine was suggested to have potent anti-arthritic and anti-inflammatory effects in rat models [ 52 ]. The other drug candidates that were indirectly linked to rheumatic diseases were racecadotril (enrichment score = 0.67 and p = 2.47 × 10 −02 ) and streptozocin (enrichment score = 0.65 and p = 3.34 × 10 −02 ).…”
Section: Resultsmentioning
confidence: 99%
“…A change in rheumatoid indices as right hind paw circumference, paw volume, and paw thickness has been utilized for assessing the anti-inflammatory effects on RA (Ali et al, 2016;Chen et al, 2017;Eiseman et al, 1982). In the present investigation, these rheumatoid indices were measured to assess the anti-arthritic activity of lemon and grapefruit peel hydroethanolic extracts at the dose level of 100 mg/kg/bw in arthritic rats.…”
Section: Discussionmentioning
confidence: 97%